Ներսես Շնորհալու ծննդյան թվականն ըստ իր եղբորորդի Գրիգորի հիշատակարանի - Մաթևոսյան, Կարեն
The date of birth of Catholicos Nersēs Shnorhali (1166–1173) in Armenian studies is placed between 1098 and 1102, since direct evidence has not been known. The most commonly used wording is "around 1100." However, in the "Miscellany" of 1294 (Matenadaran, № 2496, scribe Kirakos) which contains the works of Nersēs Shnorhali, a memorable note of Grigor, the son of Shnorhali’s brother, is preserved. It mentions that he became catholicos at the age of 56, occupied the throne for 7 years and died at the age of 63. Since the dates of accession to the throne and death of the Catholicos are known (1166 and 1173 respectively), then the date of his birth upon accession to the throne should be 1110 (1166 – 56 = 1110, and based on the year of his death, 1173 – 63 = 1110). This date differs significantly from those common in literature. The author of the colophon is either the direct successor of Nersēs Shnorhali – Catholicos Grigor Tgha (1173–1193), the son of Shnorhali’s elder brother Vasil, or Catholicos Grigor Apirat (1194–1203), the son of another brother, Zoravar. Дата рождения католикоса Нерсеса Шнорали (1166-1173) в исследованиях до сих пор отмечается в промежутке 1098-1102 гг., так как прямых свидетель- ств о ней не было. Чаще всего используется формулировка «около 1100 г.». Однако в "Сборнике" 1294 г. (Матенадаран, № 2496, переписчик Киракос), со- держающем труды Нерсеса Шнорали, сохранилось памятная запись Григора –сына брата Шнорали, где упоминается, что он стал католикосом в возрасте 56 лет, занимал престол в течение 7 лет и умер в возрасте 63 лет. Поскольку даты вступления на престол и смерти католикоса известны, соответственно – 1166 и 1173 годы, то и дата его рождения по вступлению на престол (1166-56=1110) получается 1110 год, а по дате смерти (1173-63=1110) тоже 1110 год. Как ви- дим, эта дата существенно отличается от дат, распространенных в литературе до сих пор. Автором памятной записи является либо непосредственный преемник Нерсеса Шнорали - католикос Григор Тга (1173-1193), сын старшего брата Шнорали – Василия, либо сын другого брата – Зоравара, католикос Григор Апират (1194-1203).
Keywords: Պատմություն